Cél vagy eszköz? : a magyar EU-tagság néhány tapasztalata - Gazdag, Ferenc (Közép-Európai Közlemények, 2015)
International organisations, founded by national governments create basic network of international life and politics. From the point of view of small or medium size countries memberships reflect largely the capabilities of states for national interests. All former socialist countries expressed immediately after 1989 their aspirations to become full fledges members in organisations like European Council, NATO or European Union. So did Hungary being one of the leader in the political-economic changes in Central Europe. Due to very different reasons EU enlargement with 10 new members happened only in 2004, after ten years of preparation. This article try to set up an early balance sheet of the Hungarian experience accumulated in these years including the first EU Council Presidency.